Speech text of conference of heads of academic departments (CHAD) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
CHAD 2023 is an annual event held by Universiti Teknologi MARA (UiTM) which brings together academic leaders from different faculties, centres, and branches from all over the country. The conference functions as an excellent platform for our leaders to exchange ideas, best practices, and experiences in managing and improving the quality of higher education.